Team up for better learning: evaluating team-based learning in anatomy education - Nurhadi, Asty Amalia; Jones, Linda; Budu, Budu (Institute of Advanced Engineering and Science, 2025)
This study evaluated the effectiveness of team-based learning (TBL) in teaching musculoskeletal anatomy compared to traditional lectures. A total of 267 second-year medical students participated. Student performance was assessed using pre- and post-tests, and results were analyzed with a paired t-test (p<.05), revealing significantly higher anatomy scores following TBL. Student perceptions were explored through a Likert-scale questionnaire analyzed descriptively, and focus group discussions (FGDs), which were transcribed and analyzed using thematic analysis. Students reported that TBL enhanced their understanding of musculoskeletal anatomy and added value by illustrating clinical relevance, encouraging active learning, promoting discussion and communication skills, improving motivation, and reinforcing class preparedness. TBL also fostered knowledge integration, critical thinking, and peer teaching. Despite its benefits, students noted challenges such as limited in-depth discourse, varying group dynamics, subjective peer evaluations, and logistical constraints like unsuitable room setups. Overall, the findings suggest that TBL is an effective alternative to traditional lectures in anatomy education, supporting both academic performance and the development of key competencies essential for future medical professionals.